Branquitude e ressignificação: novas propostas de análise - Martins, Lauro Geovany Damasceno (2024)
In the first part of this master's thesis, we begin our discussions within Critical Whiteness Studies, an interdisciplinary field of study that has emerged in recent decades, especially in the Brazilian context. After a short historical review of the constitution of the field (Fanon, 2008; Memmi, 1957; Ramos, 1957; Schucman, 2023; Sovik, 2009; Frankenberg, 2004; DiAngelo, 2018; Bento, 2022), we point out what may be the possible shifts based on Cardoso (2008, 2017, 2020) to think about a categorization of the discursive practices of occupants of whiteness. Both non-signatory occupants of whiteness, as we have called those who put themselves in the public space as allies in the anti-racist struggle, and those who intentionally adhere to this racial pact, can have racial practices that are sometimes more anti-racist and sometimes more racist. Breaking away from the categorization of "being anti-racist" or "being racist" allows us to think of positions that are not watertight, but porous, in terms of understanding what the contribution of occupants of whiteness to the anti-racist struggle is and can be. So, on a scale that combines a coefficient of criticality with another of agentivity, namely the critical-agentivity scale, we have listed at least six possible positions for thinking about the (non-)contribution of these subjects to the struggle. At the extreme left of the scale, indicating the highest degree of positive contribution to the struggle, we have agentive criticality, followed by performative criticality and indifferent criticality. Moving into the more racist degrees of practice, we start at the right of the scale with displaced non-criticality, meritocratic non-criticality and, finally, supremacist non-criticality. The first term of these names (criticality or non-criticality) refers to the presence or absence of self-questioning about the privileges received, not just the recognition or not of receiving these symbolic and material advantages. Consequently, the second term of these names elucidates the categorization of the types of agentivity that these subjects can exercise, ranging from a more anti-racist social action to a more racist one. By categorizing the racial practices of the occupants of whiteness, and not, as is common, the subjects themselves, we remove the possibility of thinking in closed, watertight, immutable denominations, almost always based on fragile arguments, to start with a detailed analysis of what is supra-individual and, consequently, for everyone to do or avoid. In the second part of this paper, we will deal with Discursive Resignification as a theoretical apparatus - Resignification, as a movement of the subalternized classes, is not something new in the public space. Several studies have applied the theory of discursive resignification in order to test the effectiveness of this device (Baronas, 2024; Ponsoni, 2023; Baronas, Costa, Fabiano, 2022; Baronas, 2021; Costa, 2021a; Costa, 2021b; Baronas, Costa, Conti, 2021). All of them, with great success, reveal to us the pertinence of theorizing and working with a theoretical apparatus of such revolutionary power, since it serves as an instrument for the emancipation of socio-historically marginalized groups. This process of reversing the values of certain linguistic forms that are used to offend marginalized subjects is now theorized within the scope of linguistic-discursive studies and operates, according to Paveau (2021a), guided by seven linguistic-techno-discursive criteria. This theoretical paper aims to present the motivations for considering an eighth criterion for this theoretical device, here called the intersectional criterion. To this end, we have aligned ourselves with the theoretical-methodological assumptions of French discourse analysis, more specifically those of Digital Discourse Analysis (Paveau, 2021a), with the aim of reflecting exclusively on the theoretical proposal of discursive re-signification, and not on the uses that materialize this theory. To this end, it is worth pointing out that Digital Discourse Analysis operates under three main pillars that are sine qua non for thinking about discursive re-signification: (1) the ecological approach to discursive production; (2) the symmetrical view of linguistic materialities and (3) the post-dualist perspective. These three components lead us to think of a new way of working with digital discourse - no longer conceiving of it as a discourse allocated to the digital, but a discourse that is digitally native, that is constituted together with the digital. The two proposals presented in this paper are justified by the need to think of new categories that take into account, with a greater degree of totality, the social phenomena that are emerging, especially those that take place in the digital world.